Phylogeography of Scots pine in Europe and Asia based on mtDNA polymorphisms. Issue 2 (10th October 2022) - Wachowiak, Witold; Żukowska, Weronika B.; Perry, Annika; Lewandowski, Andrzej; Cavers, Stephen; Łabiszak, Bartosz
Abstract: We analyzed mitochondrial DNA polymorphisms to search for evidence of the genetic structure and patterns of admixture in 124 populations ( N  = 1407 trees) across the distribution of Scots pine in Europe and Asia. The markers revealed only a weak population structure in Central and Eastern Europe and suggested postglacial expansion to middle and northern latitudes from multiple sources. Major mitotype variants include the remnants of Scots pine at the north‐western extreme of the distribution in the Scottish Highlands; two main variants (western and central European) that contributed to the contemporary populations in Norway and Sweden; the central‐eastern European variant present in the Balkan region, Finland, and Russian Karelia; and a separate one common to most eastern European parts of Russia and western Siberia. We also observe signatures of a distinct refugium located in the northern parts of the Black Sea basin that contributed to the patterns of genetic variation observed in several populations in the Balkans, Ukraine, and western Russia. Some common haplotypes of putative ancient origin were shared among distant populations from Europe and Asia, including the most southern refugial stands that did not participate in postglacial recolonization of northern latitudes. The study indicates different genetic lineages of the species in Europe and provides a set of genetic markers for its finer‐scale population history and divergence inference. Abstract : The distribution of various mitochondrial DNA haplotypes (marked in different colors) of Scots pine in Europe and Asia has been studied. Major mitotype variants include the remnants of Scots pine at the most western distribution of the species that colonized the Scottish Highlands, the main variants (western and central European) that contributed to the contemporary populations in Norway and Sweden, the central‐eastern European variant that colonized Baltic countries, Finland, and Russian Karelia, and a separate one common to most eastern European parts of Russia and western Siberia. The study highlights the complex population history of the species that influenced the distribution of genetic variations across the species range.